Feeling good about your body : the role of self-compassion in supporting body appreciation amongst New Zealand adults : a thesis presented in partial fulfilment of the requirements for the degree of Master of Health Science in Psychology at Massey University, Auckland, Aotearoa New Zealand - Braven, Aleisha Nicole (Massey University, 2023)
In Aotearoa New Zealand, there are concerning rates of eating disorders and normativity of body discontent (Tantleff-Dunn et al., 2011; Wells et al., 2006). Research has indicated that negative body image is, in part, a consequence of exposure to societal appearance ideals that impede self-worth (e.g., appearance contingent self-worth) and body-related threats (e.g., body comparison) that people are challenged with on a daily basis. While increasing positive body image has been a proposed mechanism for reducing symptoms of eating disorders (Piran & Tylka, 2019), no research has been conducted that examines positive body image and threats to positive body image among New Zealanders. Additionally, there is a research deficit regarding the factors involved in fostering and safeguarding positive body image in New Zealanders. One factor which is shown to be related to protecting positive body image from body-related threats is self-compassion, or the ability to be kind to oneself even amid times of difficulty and suffering. Homan and Tylka (2015) investigated this phenomenon and found that self-compassion protected participants body appreciation from the threats of body comparison and appearance contingent self-worth. This study aimed to directly replicate Homan and Tylka’s (2015) study by investigating whether self-compassion would moderate the relationships between body appreciation and (a) body comparison and (b) appearance contingent self-worth. Additionally, it aimed to examine the associations between self-compassion, body appreciation, body comparison and appearance contingent self-worth in a diverse sample of Aotearoa New Zealand adults. Participants (N = 206; mean age = 34.8, SD = 12.4) completed self-report measures of self-compassion, body appreciation, body comparison and appearance contingent self-worth online via Qualtrics. Pearson’s product-moment correlation coefficient and two regression-based moderation analyses were conducted to investigate the relationships between the main study variables and to test self- compassion as a moderator. Results indicated that body comparison and appearance contingent self-worth were negatively related to body appreciation and that self-compassion was positively associated with body appreciation. However, in contrast to Homan and Tylka’s (2015) study, self-compassion did not moderate the negative relationship between body appreciation and body comparison and appearance contingent self-worth, such that self-compassion did not appear to protect participants body appreciation from the threats of body comparison and appearance contingent self-worth. These results underline the need for more research attention on positive body image and highlight self-compassion as an advantageous characteristic supporting positive body image among New Zealanders.
Keywords: body image; self-compassion; body appreciation; appearance contingent self-worth; body comparison; New Zealand; 520304 Health psychology